Evaluation of toxicity of Bilsaan stem bark extracts in Swiss Albino mice: Evaluation of acute toxicity of bilsaan - Alrumaihi, Faris (International Journal of Health Sciences, 2019)
Objective: Sambucus nigra commonly known as Bilsaan is used extensively in traditional medicine in Saudi Arabia to treat various types of illness. The establishment of safe dose of S. nigra is crucial while considering health-promoting benefits as exposure to excess amount may cause undesirable effects. The aim of the present study was to evaluate the acute oral toxicity of ethanolic (Eth) and methanolic (Meth) extracts from the bark of Bilsaan (Bil) in mice. Materials and Methods: The acute oral toxicity study of Eth-Bil and Meth-Bil extracts was carried out by the administration of 10, 100, and 1000 mg/kg body weight to mice in the 1st phase. According to the observation of the 1st phase, the Eth-Bil extract was given 50, 100, 200, and 400 while Meth-Bil was administered 200, 400, 800, and 1600 mg/kg body weight. Results: The LD50 of the S. nigra (Bilsaan) methanol and ethanol extracts in mice was determined to be 31.62 mg/kg body weight for both of the extracts as calculated by Lorke’s method. The gross observation of systemic organs demonstrated 10–90% increase in the weight of organs of animals treated with increasing concentration of extracts in comparison to control. Similarly, the hematological analyses also showed abnormality and reduction in total leukocytes count exposed with the higher concentration of extracts. Conclusions: The results indicate that the oral administration of Eth-Bil and Meth-Bil extracts produce a significant toxic effect in mice but support in the establishment of safe dose range, as the intake of high doses of S. nigra (Bilsaan) extracts may exhibit mild organ toxicity.